KOMPETENSI GURU DALAM PROSES PENETAPAN KKM PADA MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN DAN BUDI PEKERTI DI SD NEGERI MINIAPUT WAMENA - Mika Daddu Ngedi (TANGKOLEH PUTAI, 2020)
The objectives of this study were to find out the teacher's competence in the process of determining the KKM of Christian Religious Education and Character Education subjects at Wamena Miniaput Public Elementary School; (2) diagnose the obstacles faced by teachers in the establishment of KKM subjects in Christian Religious Education and Character. This study uses a qualitative analytical descriptive approach. Informants who were the source of data in this study were 3 Christian teachers of Education and Budi Pekerti subject matter and several related parties namely teachers who were included in the MGMP forum and the principal of Wamena Miniaput Elementary School. The data collection technique used is the snow ball technique. While the data analysis technique used is descriptive qualitative analysis through three flow of activities, namely data reduction, data presentation, and verification or conclusion. The results of the study showed that the teachers of Christian Education and Budi Pekerti subject matter at the Miniaput Wamena Public Elementary School did not yet have adequate competency in the KKM determination process.